LC-MS Based Phytochemical Profiling towards the Identification of Antioxidant Markers in Some Endemic Aloe Species from Mascarene Islands - Célia Breaud; Laura Lallemand; Gary Mares; Fathi Mabrouki; Myriam Bertolotti; Charlotte Simmler; Stéphane Greff; Morgane Mauduit; Gaëtan Herbette; Eldar Garayev; Christophe Lavergne; Maya Cesari; et al. (MDPI AG, 2022)
Aloe plant species have been used for centuries in traditional medicine and are reported to be an important source of natural products. However, despite the large number of species within the Aloe genus, only a few have been investigated chemotaxonomically. A Molecular Network approach was used to highlight the different chemical classes characterizing the leaves of five Aloe species: Aloe macra, Aloe vera, Aloe tormentorii, Aloe ferox, and Aloe purpurea. Aloe macra, A. tormentorii, and A. purpurea are endemic from the Mascarene Islands comprising Reunion, Mauritius, and Rodrigues. UHPLC-MS/MS analysis followed by a dereplication process allowed the characterization of 93 metabolites. The newly developed MolNotator algorithm was usedfor molecular networking and allowed a better exploration of the Aloe metabolome chemodiversity. The five species appeared rich in polyphenols (anthracene derivatives, flavonoids, phenolic acids). Therefore, the total phenolic content and antioxidant activity of the five species were evaluated, and a DPPH-On-Line-HPLC assay was used to determine the metabolites responsible for the radical scavenging activity. The use of computational tools allowed a better description of the comparative phytochemical profiling of five Aloe species, which showed differences in their metabolite composition, both qualitative and quantitative. Moreover, the molecular network approach combined with the On-Line-HPLC assay allowed the identification of 9 metabolites responsible for the antioxidant activity. Two of them, aloeresin A and coumaroylaloesin, could be the principal metabolites responsible for the activity. From 374 metabolites calculated by MolNator, 93 could be characterized. Therefore, the Aloe species can be a rich source of new chemical structures that need to be discovered.